Formal Synthesis of Teadenols via Palladium-Catalyzed 6-endo Cyclization of an Epoxyphenol - Kitamura, Mitsuru; Suetake, Hiroki; Hoshino, Kosuke; Higashijima, Yuta; Kisanuki, Masato; Yuasa, Ryohei; Yamaguchi, Yukihiro; Shimazu, Takahiro; Koga, Naoya; Hamada, Hiro; Miyori, Nobuhiro; Shimooka, Hirokazu; Okauchi, Tatsuo (Synlett, 2022)
Formal syntheses of teadenols A and B are achieved via a key Pd-catalyzed 6-endo cyclization of a phenol possessing a vinyl epoxide moiety. Although 5-exo and 6-endo cyclizations compete during cyclizations of epoxides with a nucleophilic moiety at the 5-position, 6-endo cyclization is realized by using a palladium catalyst.
Keywords: 6-endo cyclization; formal synthesis; palladium; teadenol; vinyl epoxide